Systematic design of a maximum water recovery network for an urban system based on pinch analysis - Wan Alwi, Sharifah Rafidah; Abd. Manan, Zainuddin; Ujang, Zaini (The Institution Of Engineers, Malaysia, 2006)
Pinch Analysis has been an established systematic technique for optimal design and retrofit of heat, mass and water recoverynetworks in industry to achieve maximum energy as well as mass efficiency. Until today, the application of Pinch Analysis is perceived to exclusively belong to the domain of process industry. This work represents a shift in the current process engineering paradigm to allow Pinch Analysis application to be extended beyond the frontiers of process industry. Two key developments related to the extension of Pinch Analysis technique to the urban sector has been presented. One is as per the establishment of the minimum water targets using the new water cascade analysis technique; and two, the adaptation of the source-sink mapping technique for the design of a maximum water recovery network to an urban system to achieve the water targets. Application of these techniques on Sultan Ismail Mosque in Universiti Teknologi Malaysia yields potential maximum reductions of 85.5% fresh water and 67.7% wastewater.